Examining investment initiative in Takaful operation: issues, constraints and the way forward - Abdullah, Nurdianawati Irwani; Ali, Mohammad Mahbudi; Jinnah, Muhammad Ali; Md. Zuki, Ahmad Mazrul Shahir; Abdullah, Syahida ([s.n.], 2012)
Investment activity is a new added feature in takaful operations nowadays, departing from its original role: protection. The paper aims to examine the concept and mechanism of investment initiative undertaken by takaful operators (TOs). It also identifies some issues surrounding its practice, i.e Shari'ah, operational, and legal issues. The Shari'ah issues identified in the paper are inter alia the issues of income purification, fee for managing muÌÉrabah investment fund, investing Participant's Risk Fund (PRF), and fee for fund manager. Meanwhile, the prevailing operational issues addressed in this paper are limited investment avenue, investment fund monitoring, issue of participants’ involvement, investment cross borders, and asset liability mismatch. Furthermore, the legal issues highlighted in the paper are the issue of takaful structure and Shari'ah governance framework.